2014
DOI: 10.1016/j.fuel.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation and combustion of multicomponent fuel droplets

Abstract: The effects of difference in fuel components on the droplet evaporation and combustion are numerically investigated. Jet-A is used as liquid fuel, and one (n-decane)-, two (n-decane and 1,2,4-trimethyl-benzene)-and three (n-dodecane, iso-octane and toluene)-component fuels are used as the surrogate fuels of Jet-A. The results show that the evaporation of the three-component surrogate fuel becomes faster and slower than those of the one-and two-component surrogate fuels in the initial and subsequent evaporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 40 publications
(46 reference statements)
0
34
0
1
Order By: Relevance
“…In addition, it can also be found that the difference in droplet evaporation characteristics between ABE-diesel blends and diesel is mainly in the early stage of equilibrium evaporation phase because of the high volatility of ABE components. In the ABE-diesel blends droplet evaporation process, the droplet temperature quickly approaches the boiling points of ABE components, the evaporation of ABE components accelerates, which leads to the evident decrease of ABE-diesel blends droplets diameter in the early stage [27]. Furthermore, more ABE content in ABE-diesel blends leads to a faster evaporation in this stage.…”
Section: Droplet Evaporation Characteristics At 423 Kmentioning
confidence: 99%
“…In addition, it can also be found that the difference in droplet evaporation characteristics between ABE-diesel blends and diesel is mainly in the early stage of equilibrium evaporation phase because of the high volatility of ABE components. In the ABE-diesel blends droplet evaporation process, the droplet temperature quickly approaches the boiling points of ABE components, the evaporation of ABE components accelerates, which leads to the evident decrease of ABE-diesel blends droplets diameter in the early stage [27]. Furthermore, more ABE content in ABE-diesel blends leads to a faster evaporation in this stage.…”
Section: Droplet Evaporation Characteristics At 423 Kmentioning
confidence: 99%
“…18,19 The CPU time for case 1 is about 5.3 million h (520 h on the wall-clock time) on the K computer (Fujitsu SPARC64TM VIIIfx processor, 10 240 cores).…”
Section: ■ Numerical Simulationmentioning
confidence: 99%
“…There are numerous evaporation models available in the literature, see, e.g., [6][7][8][9][10]. Among them, the simplest one, the D 2 -law, developed by Spalding and Godsave [11,12] is used presently.…”
Section: Introductionmentioning
confidence: 99%